Congruent morphological and genetic differentiation as a signature of range expansion in a fragmented landscape. Issue 12 (25th September 2013) - Ledevin, Ronan; Millien, Virginie
Abstract: Phenotypic differentiation is often interpreted as a result of local adaptation of individuals to their environment. Here, we investigated the skull morphological differentiation in 11 populations of the white‐footed mouse ( Peromyscus leucopus ). These populations were sampled in an agricultural landscape in the Montérégie region (Québec, Canada), at the northern edge of the distribution of the white‐footed mouse. We found a strong pattern of phenotypic differentiation matching the genetic structure across these populations. Landscape fragmentation and the presence of geographic barriers, in particular north–south oriented rivers, contribute to this differentiation and modulate the pattern of rapid ongoing northward range expansion of the white‐footed mouse in response to climate warming. We conclude that while large rivers and postglacial recolonization routes have shaped the current pattern of distribution and differentiation of white‐footed mouse populations, further local differentiation is occurring, at the scale of the landscape. We posit that the northern expansion of the white‐footed mouse is achieved through successive independent founder events in a fragmented landscape at the northern range edge of the species. The phenotypic differentiation we observe is thus a result of a number of mechanisms operating at different spatial and temporal scales. Abstract : Morphological and genetic differentiation in white‐footed mouse populations from forest patches in a fragmented landscape are congruent. This differentiation is occurring in an area located at the most northern edge of the range of the mouse.